2018
DOI: 10.12659/msm.906210
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Hearing Following Cochlear Implantation Using Different Steroid Therapy Regimens: A Prospective Clinical Study

Abstract: BackgroundA prospective clinical study was conducted to assess different regimens of steroid therapy and preservation of hearing following cochlear implantation.Material/MethodsStudy participants were ≥18 years-of-age, with a cochlear duct length ≥27.1 mm measured by computed tomography (CT), with hearing sound levels in the range of 10–120 decibels (dB) and sound frequencies of 125–250 hertz (Hz); sound levels of 35–120 dB and frequencies of 500–1,000 Hz; sound levels of 75–120 dB and frequencies of 2,000–8,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 23 publications
0
44
0
2
Order By: Relevance
“…In the longer term, however, only minimal efficacy was shown (5). Other studies have therefore concentrated on the use of prolonged steroid therapy using combined oral and intravenous steroids to stabilize and preserved hearing in cochlear implantation (6). Another approach proven more effective than single-dose steroids was the use of a perioperative oral steroid taper on low frequency hearing preservation (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the longer term, however, only minimal efficacy was shown (5). Other studies have therefore concentrated on the use of prolonged steroid therapy using combined oral and intravenous steroids to stabilize and preserved hearing in cochlear implantation (6). Another approach proven more effective than single-dose steroids was the use of a perioperative oral steroid taper on low frequency hearing preservation (7).…”
Section: Introductionmentioning
confidence: 99%
“…Another approach proven more effective than single-dose steroids was the use of a perioperative oral steroid taper on low frequency hearing preservation (7). Hence, it has already been shown clinically that a perioperative steroid application has, to some extend, a positive effect on residual, low frequency hearing (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental studies in animals have demonstrated that the use of corticosteroids is able to preserve hearing thresholds, increase the survival of hair cells and spiral ganglia, and decrease the formation of new fibrotic tissue within implanted cochlea (20)(21)(22)(23)(24)(25)(26)(27). Clinical studies demonstrate lower impedances and improved preservation of low-frequency residual hearing in patients when corticosteroids are used in CI surgery (28)(29)(30)(31)(32)(33)(34). The efficacy is attributed to the anti-apoptotic and anti-inflammatory properties of glucocorticoids, by inhibiting immune cells and decreasing the release of inflammatory factors.…”
Section: Introductionmentioning
confidence: 99%
“…Hearing sound levels of 35-120 dB and frequencies of 500-1000 Hz 3. Hearing sound levels of 75-120 dB and frequencies of 2000-8000 Hz [18] Exclusion criteria included suffering from severe diseases when the steroid treatment could worsen the patient's condition or when there would be a possibility of interaction between medication intake by patients and steroids. Nonparametric tests were used in the study due to discrepancies in the number of participants between all subgroups, small number of participants in the study, and violation of normal distribution of pure tone audiometry results [18].…”
Section: Methodology Of the Study: Primary And Secondary Outcomes Andmentioning
confidence: 99%